Telocytes play a key role in prostate tissue organisation during the gland morphogenesis - Sanches, Bruno D. A. (2017)
Telocytes are CD34-positive interstitial cells, known to exert several functions, one of which is a role in tissue organisation, previously demonstrated by telocytes in the myocardium. The existence of telocytes in the prostate has recently been reported, however, there is a lack of information regarding the function of these cells in prostate tissue, and information regarding the possible role of these cells in prostatic development. This study used immunofluorescence techniques in prostate tissue and prostatic telocytes in culture to determine the relationship between telocytes and prostate morphogenesis. Furthermore, immunofluorescent labelling of telocytes was performed on prostate tissue at different stages of early postnatal development. Initially, CD34-positive cells are found at the periphery of the developing alveoli, later in the same region, c-kit-positive cells and cells positive for both factors are verified and CD34-positive cells were predominantly observed in the interalveolar stroma and the region surrounding the periductal smooth muscle. Fluorescence assays also demonstrated that telocytes secrete TGF-β1 and are ER-Beta (ERβ) positive. The results suggest that telocytes play a changing role during development, initially supporting the differentiation of periductal and perialveolar smooth muscle, and later, producing dense networks that separate alveoli groups and form a barrier between the interalveolar region and periurethral smooth muscle. We conclude that telocytes play a relevant role in prostate tissue organisation during postnatal development.